Effect of Cold Compression and Heat Treatment on Microstructure and Mechanical Properties of Al-Zn-Mg-Cu Alloyure and mechanical properties of Al-Zn-Mg-Cu alloy - Xiaodong ZHAO; Wenjie WANG; Yueping FANG; Yajie LI; Fengming QIN (Medžiagotyra)
The microstructural evolution of Al-Zn-Mg-Cu alloy under different stress and aging temperature was studied using cold compression and heat treatment. The relationship between the process parameter and the microstructure of the material was analyzed by OM, EBSD, and TEM. The results showed that the grain size decreased and the recrystallization fraction increased with the increase of compression. Textures of <111>||X (cubic), <110>//Y, Goss have higher intensity after solution treatment, but their intensity and proportion also decrease with the increase of compression. η' is the main precipitate in the alloy aged at 140 °C, while η is the main precipitate in the alloy aged at 160°C. Precipitation coarsening and grain refinement affect the microhardness of the alloy together.